Maintenance Management Model under the TPM approach to Reduce Machine Breakdowns in Peruvian Giant Squid Processing SMEs - Gallesi-Torres, A. (2020)
In recent years, the giant squid processing industry in Peru exhibited a 59% increase in exports with respect to 2018. According to estimates, this industry generates approximately 30,900 jobs per year. However, some SMEs experience low productivity, such as the PECEPE company, due to plant downtime. This represents 26% of the available time, which translates into the loss of 1760 tons every year. The most constraining external factor the sector faces is uncertainty in resource availability caused by changing weather conditions and informal fishing activities. Although there is a large number of research studies on the fishing industry and resource extraction, literature on processing plant operations is scarce. Within this context, this study seeks to promote a high impact sector in Peru, as well as fostering processing plant competitiveness and productivity. Hence, to address these issues, the authors propose a maintenance management model under the TPM approach. As part of the results from model implementation, a 39% decrease was reported in plant downtime, while maintenance costs also decreased by 16%, which, in turn, increased machine availability and production by 784 tons per year.